Development of an internet of things microstrip antenna for turbo code off-grid emergency communications - Jr., Fredelino A. Galleto; Africa, Aaron Don M.; Bedruz, Rhen Anjerome; Peradilla, Marnel; Barja, Samuelle P.; Macariola, Sean Bono L.; Manalo, Matthew Luigi N.; Ongkinglok, Angiolo C. (Bulletin of Electrical Engineering and Informatics, 2025)
Technologies and other things are fully automated, meaning signal processing and microstrip antennas for communication are essential because of their compact size and versatility. Due to inefficiency and other factors, traditional communication methods fail, which means some emergency communication systems encounter difficulties. MATLAB was used to simulate a microstrip antenna for turbo code off-grid emergency communication and signaling of internet of things (IoT) devices. A criterion is followed to determine whether a microstrip antenna’s behavior meets the emergency communication requirements. The results show that the system’s transfer function satisfies the required conditions to meet efficient communication and signaling, especially in emergencies. The step response peaked at 1.04 and an overshoot of 4.6%, meeting the conditions for efficient communication. Besides that, the generated Bode plot and Nyquist plot display the required behavior, meaning that the microstrip antenna can function as a communication device for emergency situations.